Comparing the Amount of 25-Hydroxy Vitamin D3 Concentrated in Serum of Normal and Overweight/ Obese Women and Its Relation to Metabolic Syndrome - farzad roshanzamer; Homeyra Hamayeli Mehrabani; Mohammad Hasan Meshkibaf; Mahdi Mahmoodi; Rezvan Bizhani; Alireza Khorshid (Fasa University of Medical Sciences, 2014)
Background ; Objective: The relationship between vitamin D3 and risk factors of metabolic syndrome is unclear. This study aimed to investigate the vitamin D3 kevel of women and its relation with metabolic syndrome risk factors. Materials & methods: A cross-sectional study conducted between 200 healthy women aged 20 to 50 in two groups of normal BMI (BMI=18.5-24.9 kg/m2) and overweight/obese group (BMI≥25 kg/m2) who did not use mineral and vitamin supplementation. A fasting blood sample after 10 to 12 hour collected for fasting blood glucose, triglyceride, HDL-cholesterol and vitamin D3(25 OH D3) and weight, height, waist circumference, systolic and diastolic blood pressure were measured. Results: The mean of 89 obese subjects and 76 normal weight ones were 36±9 years old. The mean of 25 hydroxy vitamin D3 was not significantly different between the two groups 22.3±19.9 ng/ml for normal weight group and 16.5±11.4 ng/ml for the obese one (p=0.31). HDL-cholesterol (r=.25, p<0.05) and waist circumference (r=-.14, p<0.05) were related to vitamin D3 levels significantly which repeated after BMI (body mass index) adjustment Conclusion: The results indicated that although the total amount of vitamin D3 were not significantly different between the two groups but more than 80 percent of women in both groups were deficient in vitamin D3 which is a  noteworthy issue based on the findings of the study.